Treatment of carotid stenosis: surgery and stent in comparison. (8th October 2021) - Giudice, Rocco; Spataro, Claudio
Abstract: Carotid stenosis in the extracranial tract determines 10–15% of all ischaemic strokes. The aim of treatment, therefore, is to prevent major neurological events. Carotid endarterectomy surgery has proved effective in this regard, with various randomized studies that have demonstrated its validity in both symptomatic and asymptomatic patients. As an alternative, since the late 1990s, the endovascular treatment of carotid stenosis by stenting has gradually established itself. Numerous controlled clinical trials have compared surgery and carotid stenting in terms of perioperative outcomes (death, stroke, and myocardial infarction within 30 days of the procedure) and stroke prevention ipsilateral to the lesion treated during follow-up, evaluating both symptomatic and asymptomatic patients. From the systematic review of the data, it is legitimate to state that stenting may represent a safe alternative to conventional surgery in patients with symptomatic carotid stenosis under the age of 70, while endarterectomy is clearly safer and more effective than endovascular treatment for symptomatic older patients. On the other hand, as regards asymptomatic patients, the available evidence is limited and further data are needed to compare the two methods and to compare them with the best current medical therapy in order to draw conclusions.